The Impact and Mechanism of Methylated Metabotropic Glutamate Receptors 1 and 5 in the Hippocampus on Depression-Like Behavior in Prenatal Stress Offspring Rats - Lin, Tianwei (J Clin Med, 2018)
An increasing number of epidemiological investigations and animal models research suggest that prenatal stress (PS) could cause depression-like behavior in the offspring, which is sex specific. However, the underlying mechanisms remain to be elucidated. This study is to investigate the promoter methylation of metabotropic glutamate receptor 1 (mGluR1) and metabotropic Glutamate Receptor 5 (mGluR5) gene modification on PS induced depression-like behavior in offspring rats (OR). PS models were established, with or without 5-aza-2′-deoxycytidine (5-azaD, decitabine) treatment. Animal behavior was assessed by the sucrose preference test (SPT), forced swimming test (FST), and open field test (OFT). The mRNA and protein expression levels of mGluR1 and mGluR5 in the hippocampus of offspring were detected with quantitative real-time PCR and Western blot analysis, respectively. The promoter methylation in the hippocampus of mGluR1 and mGluR5 OR were also analyzed. SPT showed significantly reduced sucrose preference in PS induced OR. FST showed significantly prolonged immobility time in PS induced OR. OFT showed significantly reduced central residence time in PS induced OR and no significantly influence in rearing as well as in frequency of micturition. Moreover, the mRNA, protein expression levels, and gene promoter methylation level of mGluR1 and mGluR5 in the hippocampus were significantly increased in the PS induced male OR, while no significantly influence in the PS induced female OR. Furthermore, the PS induced effects in male OR could be reversed by the microinjection of 5-azaD. In conclusion, our results showed that the promoter methylation of mGluR1 and mGluR5 gene modification is only involved in PS induced depression-like behavior in male OR in a sex-specific manner. These findings might contribute to the understanding of the disease pathogenesis and clinical treatment in future.